Assessing the impacts of sea level rise on sand exploitation in the Can Gio Coastal Area (Vietnam) - Dang Thuong Huyen; Bui Trong Vinh.; Huynh Trung Tin.; Le Thanh Phong; Shinichi Aoki.; Ichiro Deguchi
To assess the impacts of sea level rise and sand exploitation activities in the Can Gio coastal area as well as artificial beaches, this research carries out. Numerical modelling was carried out to assess the effects of sand exploitation coupled with sea level rise on the Can Gio coastal area. The research showed that sand exploitation activities have led to erosion in the study area.
Keywords: Can Gio coastal area; Climate change; Coastal erosion; Numerical model; Sand exploitation